1997
DOI: 10.1111/j.1751-908x.1997.tb00528.x
|View full text |Cite
|
Sign up to set email alerts
|

Re‐Os Isotopic Measurements at the Femtomole Level in Natural Samples

Abstract: Here we describe a new chemical separation method for Os and an improved mass spectrometric procedure for Re and Os. This technique is based on the selective extraction of OsO4 from aqueous solution in liquid bromine. Among other advantages, this procedure avoids the cumbersome distillation procedure for Os and uses only commercial “off the shelf” PFA teflon labware. Blank levels for 0.5 g sample sizes are: 0.06 pg and 0.5 pg for Os and Re respectively. Samples containing as little as 1 pg g−1 Os can be analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
330
0
10

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 659 publications
(353 citation statements)
references
References 27 publications
(39 reference statements)
2
330
0
10
Order By: Relevance
“…Isotopic tracers ( 185 Re and 190 Os) were added to samples prior to dissolution. Os was purified using CCl 4 and HBr, micro-distilled for 3 h [43] and dried to 3 L. Os-isotope measurements were carried out by N-TIMS [44,45] with a Thermo Finnigan Triton.…”
Section: Analytical Methods and Resultsmentioning
confidence: 99%
“…Isotopic tracers ( 185 Re and 190 Os) were added to samples prior to dissolution. Os was purified using CCl 4 and HBr, micro-distilled for 3 h [43] and dried to 3 L. Os-isotope measurements were carried out by N-TIMS [44,45] with a Thermo Finnigan Triton.…”
Section: Analytical Methods and Resultsmentioning
confidence: 99%
“…Moreover, the bulk of ureilite HSE are hosted in interstitial metal phases (Janssens et al, 1987) and the high-temperature igneous processing of ureilites precludes the occurrence of highly refractory primordial HSEbearing alloys as observed for example in CAIs (Becker et al, 2001), or other refractory phases as observed in unequilibrated bulk chondrites (Brandon et al, 2005b). After digestion, Os was extracted from the reverse aqua regia using carbon tetrachloride solvent, then back extracted into HBr (Cohen and Waters, 1996), and finally purified by microdistillation (Birck et al, 1997). Following Os extraction, the aqua regia solutions were dried down and converted into chloride form, dissolved in 0.15N HCl, and loaded onto cation exchange columns for Re separation and purification (Puchtel and Humayun, 2001).…”
Section: Analytical Techniquesmentioning
confidence: 99%
“…Appropriate amounts of mixed 185 Os and 191 Pt-105 Pd spikes and sample powders (0.09 to 0.26 g for Wudi peridotites and 0.08 to 0.51 g for Fuxin peridotites) were sealed, along with 2 ml of concentrated Teflon-distilled HCl and 3.5 ml of concentrated Teflon-distilled HNO 3 into a pre-cleaned, chilled, thick-walled borosilicate Carius tube, and heated to 270°C for N 72 h. Osmium was extracted immediately from the acid solution after digestion by solvent extraction into CCl 4 , then back extracted into HBr (Cohen and Waters, 1996), and finally purified via microdistillation using a H 2 SO 4 -dichromate solution into 15 μl of concentrated HBr (Birck et al, 1997). Iridium, Ru, Pt, Pd and Re were separated and purified from the remaining acid solution using anion exchange column chromatography (Rehkämper and Halliday, 1997).…”
Section: Whole-rock Re-os Isotope and Pge Abundance Analysesmentioning
confidence: 99%